2023
DOI: 10.1186/s12891-023-06566-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of radial head fractures treated with pre-curved metacarpal plate

Xiang Yang,
Jiang Zhuang,
Zhi Xiaosong
et al.

Abstract: Objective To explore the clinical outcomes of MasonII/III radial head fractures without the neck involvement treated with pre-curved metacarpal plates. Methods Ninety cases of Mason typeII/III radial head fractures without the neck involvement were retrospectively collected from the department of orthopaedics of our hospital from September 2015 to May 2021. Group A (n = 44) underwent open reduction and internal fixation with pre-curved metacarpal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Maintaining the stability of radial head fractures remains a challenge for orthopedic surgeons due to the potential to cause problems such as combined elbow injuries ( Mellema et al, 2016 ). Studies have shown that a MTP and HCCs have favorable biomechanical outcomes in fixing axially unstable radial head fractures ( Demiroglu et al, 2016 ; Yang et al, 2023 ; Zhang et al, 2023 ). However, it is uncertain whether MTP or HCCSs have a biomechanical advantage in fixing transversely unstable radial head fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintaining the stability of radial head fractures remains a challenge for orthopedic surgeons due to the potential to cause problems such as combined elbow injuries ( Mellema et al, 2016 ). Studies have shown that a MTP and HCCs have favorable biomechanical outcomes in fixing axially unstable radial head fractures ( Demiroglu et al, 2016 ; Yang et al, 2023 ; Zhang et al, 2023 ). However, it is uncertain whether MTP or HCCSs have a biomechanical advantage in fixing transversely unstable radial head fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of complications such as internal fixation failure ( Xu et al, 2020 ) and fracture nonunion ( Golinvaux et al, 2020 ) remain high, and the initial stability of the fracture break is one of the main influencing factors. In the past, such fractures were fixed with plates, especially mini-T plates (MTPs), because of their small size, thin plate surface, and simple application ( Yang et al, 2023 ). Moreover, plates have been shown to lead to favorable biomechanical outcomes in the treatment of axially unstable radial head fractures ( Yang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation